Protection of Papuan Native Children Conflicting with Law through a Restorative Justice Approach - Mulyadi Alrianto Tadjuddin; Yuldiana Zesa Azis (Musamus Law Review, 2018)
rime can occur anywhere and anytime and can be done by anyone. Both adults, young people and even children. Even though the crimes committed by children and adults are the same, however different forms of treatment need to be taken. Especially for children in Papua with all kinds of limitations and shortcomings they have. For this reason, special treatment or special treatment is needed for children in conflict with the law. This study aims to hope that in the future the form of handling restorative justice will be put forward in dealing with criminal cases committed by children. So that children in conflict with the law are better protected by this form of handling.